PENGARUH CARA PENANAMAN DAN DOSIS PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA DAUN (Lactuca sativa L.) - Prastowo, Bayu -; Patola, Efrain -; -, Sarwono - (Innofarm:Jurnal Inovasi Pertanian, 2013)
The research of " THE INFLUENCE OF   CULTIVATION METHOD  AND THE DOSAGE OF FERTILIZER   UREA TO GROWTH AND YIELD OF LEAF LETTUCE CROP (Lactuca sativa L.)" have been done to start December 19th 2012 until January 23th 2013   at greenhouse of agriculture faculty of Slamet Riyadi University which is located in Village Kadipiro, Subdistrict Banjarsari, Town Surakarta, Province Central Java. The purpose of research was to know the influence of planting method, the influence of dosage of fertilizer urea, and its influence of interaction to growth and yield of lettuce crop. Research use elementary design the Completely Randomized Design (CRD) factorial, consist of 2 treatment factor and 3 replications. Data  analyzed  to  use  Analysis  of  Variance  (Anova),  continued  with  Honestly Significant Difference Test (HSD) on 5% significant level. The result of the research, are: 1) method of cultivation have the influence to growth and yield of leaf lettuce crop, method of  cultivation the best is the direct cultivation because it can increase of height the crops, width of leaves,  length of leaves, number of leaves, fresh weight the crop, a dry weight the crop, and net weight the consumption significantly, 2 giving  the fertilizer urea with dosage 1,2 g / polybag have an influence the  best to growth and the yield of leaf lettuce because it can increases height  of  crop, width of leaves, length of leaves,, number of leaves, fresh weight of the crops, a dry weight of the crop, and the net weight of consumption, and 3) influence of interaction  only happened at  height of crops  and its interaction influence differ in each treatment level. At level   of dosage urea, influence of interaction   between dosage 0,4 g / polybag with direct cultivation, influence of interaction  between dosage 1,2 g / polybag with direct cultivation, and iinfluence of interaction  between  dosage 1,6 g / polybag with direct cultivation. is the best. While at level of method of cultivation,  influence of interaction between way of direct cultivation with dosagee 1,2 g / polybag is the best. Key words: dosage, urea fertilizer, leaf lectuce